2018
DOI: 10.1155/2018/4931852
|View full text |Cite
|
Sign up to set email alerts
|

Long-Acting Luteinizing Hormone-Releasing Hormone Agonist for Ovarian Hyperstimulation Induced by Tamoxifen for Breast Cancer

Abstract: Tamoxifen treatment for breast cancer may induce ovarian cysts and supraphysiological levels of serum estrogen. We report successful management with luteinizing hormone-releasing hormone (LHRH) agonist of ovarian hyperstimulation induced by tamoxifen. A 49-year-old woman was operated on for invasive ductal carcinoma of the right breast. She received breast irradiation and adjuvant tamoxifen therapy. After 2 years, she had a cystic ovarian mass, and her serum concentration of estradiol was 1280 pg/mL. She was t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 19 publications
(24 reference statements)
0
3
0
Order By: Relevance
“…Ovarian hyperstimulation, ovarian cyst, and supraphysiological estradiol levels due to the use of tamoxifen for breast cancer have been reported in 11-17% of the cases (12,13). In a study, the prevalence of ovarian cysts in patients using tamoxifen has been reported as 19.4% in premenopausal and 6.3% in postmenopausal women (14).…”
Section: Discussionmentioning
confidence: 99%
“…Ovarian hyperstimulation, ovarian cyst, and supraphysiological estradiol levels due to the use of tamoxifen for breast cancer have been reported in 11-17% of the cases (12,13). In a study, the prevalence of ovarian cysts in patients using tamoxifen has been reported as 19.4% in premenopausal and 6.3% in postmenopausal women (14).…”
Section: Discussionmentioning
confidence: 99%
“…6b) [13,14]. Although recent reports also pointed out the stimulatory effects TAM on the ovarian function [16,17], its precise incidence rate remains unclear. The positive rate of OHS among groups A-C (25.1%) was slightly higher than the ratio estimated in our previous report [14].…”
Section: Discussionmentioning
confidence: 99%
“…In the uterus, TAM has rare adverse effects such as endometrial carcinoma and uterine sarcoma related to estrogenic properties [7]. In addition, an increased risk of ovarian hyperstimulation, the development of ovarian cysts and supraphysiological levels of serum E2 were reported in TAM-treated women with breast cancer [8][9][10]. During the follicular phase, TAM was suggested to inhibit E2 negative feedback on the hypothalamicpituitary axis, leading to increased pituitary secretion of FSH and LH and the development of multiple follicles.…”
Section: Introductionmentioning
confidence: 99%